Impact of PCV10 on pediatric pneumococcal disease burden in Brazil: time for new recommendations? - Daniel Jarovsky; Eitan Naaman Berezin (Elsevier, 2023)
Objective: To describe the impact of the 10-valent pneumococcal conjugate vaccine on the pediatric burden of pneumococcal infections, carriage, serotype replacement, and antimicrobial resistance in Brazil since its introduction in 2010. Data source: A narrative review of English, Spanish, and Portuguese articles published in online databases and in Brazilian epidemiological surveillance databases was performed. The following keywords were used: Streptococcus pneumoniae, pneumococcal disease, conjugate vaccine, PCV10, antimicrobial resistance, and meningitis. Summary of the findings: Declines in hospitalization rates of all-cause pneumonia occurred in the target age groups and some age groups not targeted by vaccination early after the use of PCV10. Large descriptive studies of laboratory-confirmed pneumococcal meningitis and hospital-based historical series of hospitalized children with IPD have evidenced a significant impact on disease burden, in-hospital fatality rates, and admission to the intensive care unit before and after the inclusion of the vaccine. Impact data on otitis media is limited and inconsistent; the main benefit remains the prevention of complicated diseases. During the late post-vaccine years, a significant and progressive increase in high-level penicillin non-susceptibility pneumococci has been described. Since 2014 serotype 19A has been the leading serotype in all ages and was responsible for 28.2%-44.6% of all IPD in children under 5 yrs. Conclusions: PCV10 has performed a significant impact on IPD in Brazil since 2010, however, progress has been continuously hampered by replacement. Broader spectrum PCVs could provide expanded direct and indirect protection against ST19A and other additional serotypes of increasing importance if administered to children in the Brazilian National Immunization Program.